2015
DOI: 10.1002/2015gl065798
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater recharge and age‐depth profiles of intensively exploited groundwater resources in northwest India

Abstract: Intensive irrigation in northwest India has led to growing concerns over the sustainability of current and future groundwater abstraction. Environmental tracers and measurements of groundwater residence times can help quantify the renewal processes. Results from 16 paired locations show the interquartile ranges for residence times in shallow alluvial groundwater (8-50 m deep) to be 1-50 years and significantly less than those from deeper groundwater (76-160 m deep) at 40-170 years. The widespread occurrence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(32 citation statements)
references
References 55 publications
1
30
1
Order By: Relevance
“…The 157 regional groundwater piezometric head decreases and flattens in a NE-SW direction (CGWB, 158 2007), with little or no regional flow within the central and SW part of the study area. Recent 159 groundwater dating work has shown that the regional groundwater flow is now highly modified 160 by vertical leakage due to both shallow pumping for irrigation and and abstraction at depth for 161 drinking water (Lapworth et al, 2015). Regionally the groundwater recharge is dominated by 162 meteoric rainfall (Lapworth et al, 2015), however in close proximity to surface water sources 163 including canal leakage and surface water exchange have been shown to be important (Rao et 164 al., 2017).…”
Section: Study Area: Hydrogeology and Groundwater Samplingmentioning
confidence: 99%
See 2 more Smart Citations
“…The 157 regional groundwater piezometric head decreases and flattens in a NE-SW direction (CGWB, 158 2007), with little or no regional flow within the central and SW part of the study area. Recent 159 groundwater dating work has shown that the regional groundwater flow is now highly modified 160 by vertical leakage due to both shallow pumping for irrigation and and abstraction at depth for 161 drinking water (Lapworth et al, 2015). Regionally the groundwater recharge is dominated by 162 meteoric rainfall (Lapworth et al, 2015), however in close proximity to surface water sources 163 including canal leakage and surface water exchange have been shown to be important (Rao et 164 al., 2017).…”
Section: Study Area: Hydrogeology and Groundwater Samplingmentioning
confidence: 99%
“…Recent 159 groundwater dating work has shown that the regional groundwater flow is now highly modified 160 by vertical leakage due to both shallow pumping for irrigation and and abstraction at depth for 161 drinking water (Lapworth et al, 2015). Regionally the groundwater recharge is dominated by 162 meteoric rainfall (Lapworth et al, 2015), however in close proximity to surface water sources 163 including canal leakage and surface water exchange have been shown to be important (Rao et 164 al., 2017). Irrigation in this region is both from shallow groundwater sources and the Bist-Doab 165 canal system diverted from the Sutlej River.…”
Section: Study Area: Hydrogeology and Groundwater Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…These include the relative importance of site‐specific, borehole‐ scale problems due to casing breaks at abstraction well sites (I. Choudhury et al, ) and aquifer‐scale vulnerabilities (Hoque et al, ) to contamination from shallow groundwater and the long‐term impacts of intensive pumping at depth (Khan et al, ; Knappett et al, ; Michael & Khan, ; Zahid et al, ). The presence of modern tracers (e.g., tritium and chlorofluorocarbons (CFCs)) in deeper groundwater systems (typically >150 m) has been attributed to deep pumping in the BAS and in many other aquifer systems globally (Jasechko et al, ; Lapworth et al, ; McMahon et al, ; Samborska et al, ) yet considerable uncertainty remains about the scale and nature of this pumping‐induced contamination. Here we present new evidence from multiple tracers drawn from dedicated, depth‐specific piezometers and actively pumped wells in the BAS, the world's largest deltaic aquifer system, to assess pumping‐induced recharge processes within the deep fresh BAS.…”
Section: Introductionmentioning
confidence: 99%
“…For this, a groundwater monitoring network should be designed and planned scientifically in the study area 12 . The water level should be analysed quantitatively for proper planning [13][14][15][16][17][18][19] .…”
Section: Study Areamentioning
confidence: 99%